Norm, standards and tests in the structure of creation of monitoring of physical development, physical fitness and physical state - Ажиппо Олександр Юрійович, (Oleksandr Aghyppo); Дорофєєва Тетяна Іванівна, (Tatyana Dorofeeva); Пугач Ярославна Ігорівна, (Yaroslavna Puhach); Артем’єва Галина Павлівна, (Galina Artem’yeva); Нечитайло Марія Валеріївна, (Mariia Nechytailo); Друзь Валерій Анатолійович, (Valeriy Druz) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to define the structure of creation of monitoring of physical development, physical fitness and physical condition of the controlled contingent of the population. Materials and methods: the analysis of scientific literature on the research problem, the use of statistical material of anthropometrical data of the investigated contingent, the use of the marked semantic spaces for the representation of features of individual physical development and physical fitness of the investigated contingent. Results: the structure of creation of monitoring of physical development, physical fitness and physical state is presented as a basis of a statistical control of opportunities of physical potential of the population of the country. Conclusions: the certification of physical state and physical capacities of the population of the country will allow to operate purposefully physical development of the population taking into account regional, climate-geographical, social conditions in the questions of planning of its economic potential.